Penerapan Sistem Informasi Pemerintahan Daerah (SIPD) Berdasarkan Teori Technology Acceptance Model (TAM) Dalam Peningkatan Kualitas Laporan Keuangan Pada Organisasi Perangkat Daerah (OPD) Di Kabupaten Tanah Datar - Diana Etika Hairani Amri; Indrayeni Indrayeni (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the effect of perceived ease of use, perceived usefulness, attitude toward use, and behavioral intention to use on the quality of financial statements through the implementation of the Regional Government Information System (SIPD) in Regional Apparatus Organizations (OPD) in Tanah Datar Regency. This research employs a quantitative approach using a survey method. The sample consists of 89 respondents selected through judgment sampling technique. Data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that all variables in the Technology Acceptance Model (TAM) have a positive and significant effect on the quality of financial statements. This finding shows that user acceptance of SIPD plays an important role in improving the quality of local government financial statements. Therefore, optimizing the use of SIPD can support the preparation of more accurate, relevant, and reliable financial reports.